The use of noninvasive prenatal testing in obstetric care: educational resources, practice patterns, and barriers reported by a national sample of clinicians. (7th April 2016) - Farrell, Ruth M.; Agatisa, Patricia K.; Mercer, Mary Beth; Mitchum, Ariane G.; Coleridge, Marissa B.
Abstract: Objective: The aim of this study was to identify how physicians develop their knowledge base and practice patterns regarding noninvasive prenatal testing (NIPT). Methods: A survey was used to assess physicians' informational sources and practice patterns regarding NIPT. Results: While most of the 258 participants acquire knowledge about NIPT from the medical literature or didactic educational programming, 74 (28.7%) cite commercial laboratories as an initial source and 124 (47.8%) as a way to keep current with changes in NIPT. About one‐third ( n  = 94, 36.4%) seek information about ethical issues related to NIPT. Half of the OB/GYN respondents ( n  = 136, 52.7%) provide pretest counseling; fewer refer to a genetic counselor or maternal fetal medicine specialist (MFM) ( n  = 94, 34.6%, n  = 29, 11.2%, respectively). Pretest counseling content and the comfort with which participants discuss topics pertinent to patients' utilization of NIPT varied between OB/GYNs and MFMs. Conclusions: Advances in cff DNA technology emphasize the need for effective strategies for physicians to develop competency and practice patterns regarding NIPT. Study findings speak to the need for effective educational resources for obstetric providers, not just early adopters of NIPT but also for primary OB/GYNs as they serve in the role of the first point of contact for women considering their prenatal testing options. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? The achievement and maintenance of competency in clinical genetics have been an ongoing issue for obstetrician–gynecologists. Advances in prenatal genetic technologies present obstetric providers with increasing challenges to ensure that patients have the information and resources needed to make an informed choice about their testing options. What Does This Study Add? Advances in cff DNA technology emphasize the need for effective strategies for physicians to develop competency and practice patterns that enable patients to make informed choices about NIPT.